High-throughput cloning, expression, and purification - Owens, R; Nettleship, J; Berrow, N; Sainsbury, S; Aricescu, A; Stuart, D; Stammers, D (Oxford University Press, 2007)
High-throughput sequencing of eukaryotic, viral, and bacterial genomes provides a huge database of proteins with potential for structure-function analysis. In response to this opportunity, structural genomics projects have been initiated world-wide with the aim of establishing high-throughput structure determination on a genome-wide scale. Crucial to this effort has been the development of protein production technologies for the highthroughput cloning, expression, and purification of proteins. Large-scale structural genomic projects were initiated in the US and Europe, and all have emphasized parallel processing, both in terms of molecular cloning, expression, and purification, driven by the need to accommodate relatively large numbers of potential targets for structural biology at an acceptable cost. This has led to varying degrees of automation and most of the groups involved have set up semiautomated liquid handling systems to carry out some or all of their protocols. However, the protocols can equally well be carried out manually with appropriate equipment, for example multichannel pipette dispensers. The motivation to implement automation is largely to enable processes to be scaleable and sustainable as error-free operations. This chapter reviews the technical developments that have come from structural proteomics and provides protocols for carrying out cloning, expression, and purification procedures in a relatively high-throughput (HTP) and parallel approach.